A thousand years of translanguaging in the multilingual Maghreb - Gintsburg, Sarali; Baynham, Mike (Lingua Posnaniensis, 2026)
In this paper we explore the interaction between Maghrebi Darijas and Romance languages from the perspective of both historical and contemporary evidence. As Caubet 2002, following Lahlou 1991 argues, among contemporary educated populations in urban centres across the Maghreb, bilingual/multilingual interaction is the norm not the exception. Historical evidence tells us this was also the case in 11th century al-Andalus, though it is of course impossible down the centuries to reconstruct the actual interaction. We will however argue that certain surviving texts can provide an indication when analysed in terms of the constraints on conversational codeswitching such as is provided by Aabi. We start from the position that Maghrebi Darija is a special case of linguistic permeability due to its politico-geographic location on the frontier and given its thousand year history of close contact with Romance. To investigate this phenomenon in both its historical and contemporary manifestations we draw on the current construct of translanguaging, an alternative perspective on multilingual interaction to code switching as expounded in Baynham & Lee (2018) and the notion of convivencia as elaborated by Bossong in his study of linguistic conviviality and coexistence in mediaeval Andalusian poetry (Bossong 2010). We then go on to analyze this in two time slices: examining evidence of the productive convivencia/coexistence of romance and dialectal Arabic i) in the kharjas of 11th century al-Andalus as discussed by Bossong and others and ii) in the modern Maghreb music and performance scene (cf. Caubet 2002; Baynham & Gintsburg 2022). We do this here through analysis of a song by the Algerian singer Talyani and a performance of the Moroccan comedian Hanane el-Fadhili, using in both time slices translanguaging and Bossong’s notion of convivencia in our analysis. We then conclude by arguing as Heath (2020) does that for effective research into such varieties as Maghrebi Arabic, both currently and historically, it is necessary for cross disciplinary work between researchers in Arabic and its Romance contact languages, in order to fully address its sociolinguistics. We understand this as a form of disciplinary translanguaging to be undertaken in order to establish the dynamics of the convivencia/coexistence of Arabic and Romance elements in this type of data.